2020
DOI: 10.1073/pnas.1917362117
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-mediated depletion of serum l -Met abrogates prostate cancer growth via multiple mechanisms without evidence of systemic toxicity

Abstract: Extensive studies in prostate cancer and other malignancies have revealed thatl-methionine (l-Met) and its metabolites play a critical role in tumorigenesis. Preclinical and clinical studies have demonstrated that systemic restriction of seruml-Met, either via partial dietary restriction or with bacteriall-Met–degrading enzymes exerts potent antitumor effects. However, administration of bacteriall-Met–degrading enzymes has not proven practical for human therapy because of problems with immunogenicity. As the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 87 publications
(61 reference statements)
2
48
0
Order By: Relevance
“…o-rMETase originated in P. putida, where it can survive and proliferate in a wide range of pH and temperatures. Therefore, o-rMETase could have been evolved into an enzyme that can survive in the low pH of the stomach (31) which is a great advantage over a human engineered methioninase which must be injected (50).…”
Section: Resultsmentioning
confidence: 99%
“…o-rMETase originated in P. putida, where it can survive and proliferate in a wide range of pH and temperatures. Therefore, o-rMETase could have been evolved into an enzyme that can survive in the low pH of the stomach (31) which is a great advantage over a human engineered methioninase which must be injected (50).…”
Section: Resultsmentioning
confidence: 99%
“…According to this definition, establishing a methionine dependency phenotype is possible through in vitro testing using cell culture models and methionine-free culture media. In vivo strategies of methionine restriction are not efficient and decrease serum methionine by only 40 to 50% [51], which is not sufficient for obtaining complete methionine deprivation. In this setting, the use of methioninase-based strategies for methionine deprivation on xenografted nude mice models could be considered as part of a future development of our research framework [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo strategies of methionine restriction are not efficient and decrease serum methionine by only 40 to 50% [51], which is not sufficient for obtaining complete methionine deprivation. In this setting, the use of methioninase-based strategies for methionine deprivation on xenografted nude mice models could be considered as part of a future development of our research framework [51,52]. Third, according to international guidelines, IRs are performed after surgery or in definitive intent in glioblastoma, melanoma, or HCC.…”
Section: Discussionmentioning
confidence: 99%
“…By performing comparative CRISPR screens based on medium composition, it may also be possible to design cancer treatment strategies that exploit gene-nutrient interactions by coupling targeted inhibitors with either dietary or enzyme-catalyzed modulation of circulating metabolites. Notably, a number of clinical and preclinical enzymes mediate systemic depletion of specific metabolites (Cantor and Sabatini, 2012;Cramer et al, 2016;Lu et al, 2020;Patgiri et al, 2020;Triplett et al, 2018), and recent studies have shown that dietary intervention to either restrict or increase the availability of specific amino acids can affect cancer growth and chemotherapeutic efficacy (Gao et al, 2019;Kanarek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%